Volume 6 Number 2 2010
DOI: 10.18057/ijasc.2010.6.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thermal Insulation on the Energy Balance for Cold-Formed Buildings

Abstract: Two major factors contribute to the sustainability of buildings: material efficiency and energy efficiency. Material efficiency relates to the use of environmental-friendly materials and to the minimization of construction waste materials, either during construction and at the end-of-life stage of the building. Energy efficiency is currently understood as the optimization of the energy used during the operation stage of the building. This entails the energy needed for heating, cooling, lighting, etc. Often in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…When submitted the same model under the EN ISO 6946 [15] analytic calculation method, according to expressions (4) and (10), the same U-value (0.2222 W·m −2 ·K −1 ) was obtained. This second verification confirms the accuracy of this FEM software in performing thermal analysis.…”
Section: Verification Against En Iso 6946mentioning
confidence: 90%
See 2 more Smart Citations
“…When submitted the same model under the EN ISO 6946 [15] analytic calculation method, according to expressions (4) and (10), the same U-value (0.2222 W·m −2 ·K −1 ) was obtained. This second verification confirms the accuracy of this FEM software in performing thermal analysis.…”
Section: Verification Against En Iso 6946mentioning
confidence: 90%
“…According to Gervásio et al [4] two major factors contribute to the sustainability in building sector: material efficiency and energy efficiency. The same author also refers that often, to reduce operational energy needs of a building, more insulation material is used, leading to a trade-off between embodied and operational energy, which must be considered.…”
Section: Embodied and Operational Energymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the assessment of the economic and environmental benefits of thermal insulation is a challenging task. Gervásio et al [57] evaluated the influence of several levels of insulation on the energy balance of LSF buildings. The authors also discussed the balance between embodied and operational energies for different scenarios.…”
Section: Strategies For Improving the Thermal Resistance Of Lsf Elementsmentioning
confidence: 99%
“…For instance, Thormark [226] showed that about 40-60% of the life cycle energy of a building is used in the initial stages of material production and construction. In a parametric study carried out by Gervásio et al [57] on a LSF residential building located in Portugal, different levels of insulation were considered to assess the trade-off between energy efficiency and life cycle embodied energy. In this study, it was showed that 16 years were needed for the operational energy to overcome the embodied energy.…”
Section: Balance Between Embodied Energy and Operational Energymentioning
confidence: 99%